Endogenous Retinoids in Mammalian Growth Plate Cartilage: ANALYSIS AND ROLES IN MATRIX HOMEOSTASIS AND TURNOVER - Williams, Julie A. (American Society for Biochemistry and Molecular Biology, 2010)
The growth plate contains resting and proliferating chondrocytes in its upper zones (UGP) and maturing and hypertrophic chondrocytes in its lower zones (LGP), but the mechanisms by which it operates to sustain skeletal growth are not fully clear. Retinoid signaling was previously found to be nearly absent in UGP, but to be much stronger in LGP coincident with hypertrophy, extracellular matrix turnover and endochondral bone formation. To determine whether such distinct signaling levels and phenotypic events reflect different endogenous retinoid levels, the upper two-thirds and lower one-third of rabbit rib growth plates were microsurgically isolated and processed for ultrasensitive retinoid LC-tandem MS quantification. Indeed, the UGP samples contained only about a 0.6 nm concentration of all-trans-retinoic acid (atRA) that is the most active natural retinoid in tissues, whereas LGP samples contained nearly 3-fold higher atRA levels (about 1.8 nm). Perichondrium was quite rich in atRA (about 4.9 nm). Interestingly, the levels of retinol, the major but inactive atRA precursor, were similar in all tissues (1.1–1.6 μm), suggesting that the distinct atRA levels in UGP and LGP reflect different retinoid anabolic capacity. Indeed, RALDH2 and CRABP1 transcript levels were much higher in LGP than UGP samples. To determine the minimum effective atRA concentration, chondrogenic cells transfected with a retinoic acid response element (RARE)-luc reporter plasmid were treated with different concentrations of exogenous atRA (0–100 nm). About 3 nm atRA was needed to elicit appreciable RARE-luc reporter activity and to decrease proteoglycan synthesis and activity of an aggrecan enhancer reporter plasmid. In sum, the data indicate that (i) the endogenous levels of atRA are significantly higher in hypertrophic than upper zones of growth plate; (ii) such difference likely reflects distinct retinoid anabolic capacity; and (iii) importantly, atRA levels in hypertrophic portion are within effective ranges to elicit retinoid signaling and action, but those in upper zones are not.